2018
DOI: 10.1161/jaha.118.009595
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Pregnant Women Who Subsequently Develop Hypertension in Pregnancy

Abstract: BackgroundHypertensive disorders complicating pregnancy are a major cause of maternal death. Our objective was to evaluate maternal clinical, hemodynamic, and placental prognostic indicators in a consolidated manner to identify women who develop hypertension in pregnancy.Methods and ResultsTwenty‐six normotensive pregnant women from a specialized Placenta Clinic at increased risk of developing de novo hypertension and 20 normotensive healthy pregnant controls were recruited at 22 to 26 weeks' gestation. Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 34 publications
1
44
0
4
Order By: Relevance
“…Many of the latest studies have shown that, among the hemodynamic parameters, TVR and CO represent a cornerstone for the understanding of the preclinical and clinical stages of the HDP. McLaughlin et al,13 in accordance with other reports, found in their study that maternal TVR was the best single predictive factor for the development of hypertension in pregnancy, followed by endoglin, mean arterial pressure, placental growth factor, and soluble Fms‐like tyrosine kinase‐1. TVR represents the equilibrium between SV, blood pressure, and heart rate.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Many of the latest studies have shown that, among the hemodynamic parameters, TVR and CO represent a cornerstone for the understanding of the preclinical and clinical stages of the HDP. McLaughlin et al,13 in accordance with other reports, found in their study that maternal TVR was the best single predictive factor for the development of hypertension in pregnancy, followed by endoglin, mean arterial pressure, placental growth factor, and soluble Fms‐like tyrosine kinase‐1. TVR represents the equilibrium between SV, blood pressure, and heart rate.…”
Section: Introductionsupporting
confidence: 86%
“…The first one has been the uterine artery Doppler interrogation in the second trimester, and has been introduced since the past 2 decades of the past century 1. Lately, biochemical and central hemodynamic parameters have been used to refine and improve the classification and the prediction of HDP 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 13…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations